Influence of gas-to-liquid (GTL) fuel in the combined blend of Jatropha biodiesel and diesel: an analysis of engine combustion–performance–emission parameters. Issue 38 (27th March 2015) - Sajjad, H.; Masjuki, H. H.; Varman, M.; Kalam, M. A.; Arbab, M. I.; Imtenan, S.; Rashedul, H. K.
Abstract : This study presents a comparative analysis of the blends of JBD (J20) and GTL fuel (G20) with diesel, including a ternary blend of JBD-GTL-diesel (DJG20), in the context of fuel properties, engine performance and emission characteristics. Abstract : This study reports the production of Jatropha biodiesel (JBD) and a comparative analysis of the fuel properties, engine performance and emission characteristics of blends of JBD (J20) and GTL fuel (G20) with diesel, including a combined blend of JBD, GTL and diesel (DJG20). The ternary blend was selected to combine the promising properties of the two alternative fuels. In this study, a four-cylinder compression ignition engine was used to perform tests at different speeds under constant torque. DJG20 and G20 showed the most promising properties among all tested fuels. In combustion analysis, the peaks of both in-cylinder pressure and heat release rate (HRR) of G20 were lower and occurred at later crank angles compared to those of diesel. The other two blends demonstrated higher peaks of both parameters, while DJG20 showed lower peaks than J20 in both cases. The peak locations of J20 and DJG20 were slightly higher than those of diesel. The engine performance results showed an average increase in brake thermal efficiency (BTE) and lower fuel consumption (BSFC) for G20, whereas the other two blends exhibited decreases in BTE but increases in BSFC compared to diesel. The emission analysis results of all fuel blends showed lower CO, HC and smoke emissions than diesel. For NO x emissions, G20 showed a significantly decreased value, whereas the other two blends showed increased values compared to diesel. Compared to J20, DJG20 showed improvements in all performance–emission parameters.